2022
DOI: 10.3389/fonc.2022.896433
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Sterol O-Acyltransferase 1 as a Prognostic Biomarker and Its Association With Immune Infiltration in Glioma

Abstract: Metabolic reprogramming is a hallmark of glioma, and sterol O-acyltransferase 1 (SOAT1) is an essential target for metabolic therapy. However, the prognostic value of SOAT1 and its association with immune infiltration has not been fully elucidated. Using RNA-seq and clinical data of glioma patients from The Cancer Genome Atlas (TCGA), SOAT1 was found to be correlated with poor prognosis in glioma and the advanced malignancy of clinicopathological characteristics. Next, the correlation between SOAT1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…SOAT1 was downregulation in psoriasis skin lesions 50 , The function SOAT1 in psoriasis and leprosy has not been extensively studied. SOAT1 expression level was positively correlated with macrophages, neutrophils, Th17 cells, and activated dendritic cells, while negatively correlated with plasmacytoid dendritic cells or natural killer cells in glioma 51 . Inhibition of SOAT1 expression can have anti-inflammatory effects by altering free cholesterol levels or oxysterol levels 52 .…”
Section: Discussionmentioning
confidence: 93%
“…SOAT1 was downregulation in psoriasis skin lesions 50 , The function SOAT1 in psoriasis and leprosy has not been extensively studied. SOAT1 expression level was positively correlated with macrophages, neutrophils, Th17 cells, and activated dendritic cells, while negatively correlated with plasmacytoid dendritic cells or natural killer cells in glioma 51 . Inhibition of SOAT1 expression can have anti-inflammatory effects by altering free cholesterol levels or oxysterol levels 52 .…”
Section: Discussionmentioning
confidence: 93%
“…More importantly, SOAT1 expression was found to be positively correlated with multiple chemokine/chemokine receptor gene and various checkpoint genes, including PD-L1. These results indicated that SOAT1 overexpression may affect immune infiltration and tumor immune escape via increasing the secretion of chemokines and the levels of checkpoint genes ( 58 ). Nevertheless, both the mechanism by which SOAT1 promotes tumor growth and immune escape need to be further studied.…”
Section: Tumor Promotion By High Soat1 Expressionmentioning
confidence: 98%
“…ACAT1 can reduce cell proliferation and induce cell apoptosis ( 157 ). A bioinformatics study showed that the expression of ACAT1 was positively linked to macrophages, neutrophils, Th17 cells, and activated dendritic cells but negatively linked to plasmacytoid dendritic cells or natural killer cells ( 158 ). Inhibiting ACAT1 decreases the number of inflammatory monocytes and macrophages and changes them to an anti-inflammatory M2 phenotype, and blocking ACTA1 also decreases the expression of inflammatory factors like MCP-1 and CCL5/7 ( 159 ).…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%